Evolution in inter-firm governance along the transport biofuel value chain in maritime Silk Road countries - Chan, JH; Reiner, DM (Elsevier, 2019)
We investigate how value chain governance can evolve in the transport biofuel sector beyond logistics and operations optimization, drawing on cases of eighteen manufacturers in four Belt and Road countries. We find that key motivations for vertical integration include control of strategic factors such as security of supply and gaining access to the retail market, subject to inter-institutional and intra-organizational barriers. We contribute to a theory of governance mode selection by suggesting plural governance mode offers a key strategic choice under institutional constraints. In BRI countries, plural mode could be less disruptive when integrating value chains.
Keywords: Transaction cost theory; Fuel-ethanol; Global value chain; China; South East Asia; Biofuels; Belt and Road Initiative